Machining Untuk Mengatasi Ovality Pada Cylinder Transition Turbin Gas MW701D Di UP Gresik - Arief Suardi Nur Chairat; Mahmudi Mahmudi (Sekolah Tinggi Teknik - PLN, 2015)
In the gas turbine will function cylinder transition is important, therefore, the need for a replacement part is needed. At this time, the condition of the cylinder transition caused a lot of experience working padadaerah keovalan high temperature so that deformation of the material merupakanpenyebab keovalan.Akibat keovalan the transition cylinder assembly process between basketball combustors and transition piece cylinder connected with the cylinder transition becomes difficult and takes a relatively longer and yield less than the maximum. Furthermore, the process of turning cylinder oval transition so as to re-round, this process requires a cylinder that has been available in the warehouse and use the Gresik Power Unit 1 set lathe which has existed in the workshop Maintenance Service Unit of the Eastern Region and the measuring instrument. Turning is done through the same transition smallest diameter cylinder with a diameter transition piece (Ø 335 mm) After the machining process is done the testing process transition cylinder machining results, the tests performed, among others, hardness test, and penetrant testing test aims to determine whether a decline in the quality of material , and make sure no material defects occur after the machining process. Reduction of the maximum allowable thickness is 3.2 mm atau30% recommendation from manual book.